Parmenide e Platone (e Aristotele) nel Contro Colote di Plutarco - Mauro Bonazzi (Aitia, 2013)
The chapters dedicated to Parmenides and Plato play a decisive role in the composition strategy of the Adversus Colotem, since this is where Plutarch most clearly defines the background dualist thesis that will help demonstrate that Platonism is superior to Epicurism. By showing Parmenides too as a dualist engaged in distinguishing between the sensible and the intelligible world, Plutarch structures a history of ancient philosophy entirely focused on Plato. These chapters also bear witness of another centre of interest, namely Aristoteles (§ 14), who, despite the criticism he aimed at the theory of ideas, is not completely refuted, but rather used as a possible ally against epicurean materialists, Plutarch’s true bête noire.